Abadie's kappa and weighting estimators of the local average treatment effect - Słoczyński, Tymon,Uysal, Selver Derya,Wooldridge, Jeffrey M. (IZA - Institute of Labor Economics, 2022)
In this paper we study the finite sample and asymptotic properties of various weighting estimators of the local average treatment effect (LATE), several of which are based on Abadie (2003)'s kappa theorem. Our framework presumes a binary endogenous explanatory variable (
10419/263457
Keywords: Graue Literatur; Kausalanalyse; IV-Schätzung; Schätztheorie; Simulation; instrumental variables; local average treatment effects; one-sided noncompliance; weighting